Analysis and Testing of the Expansion Tank in the Rectangular Flow Channel FASSIP-04 Ver.0 - Yuliaji, Dwi; Waluyo, Roy; Alimudin, Alimudin; Hendrawan, A. H.; Hishamuddin, Hawa Bt; Juarsa, Mulya (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The expansion tank in the FASSP-04 Ver.0 Rectangular Loop functions as a reducer of pressure fluctuations during the natural circulation flow. The expansion tank function cannot work optimally if there is a leak in the welding area or the material structure is not good. So the purpose of the research conducted is to obtain a stable pressure value and material strength value. The research was conducted using experimental method and finite element analysis simulation. Experiments were carried out by applying pressure to the expansion tank from 1.5 bar to 4 bar and held for up to 1 hour. Then simulations were carried out based on variations in the input pressure given from 4 bar, 125 bar, and 154 bar. Experimental results at input pressures of 1.5 bar, 2 bar, 2.5 bar, 3 bar, 3.5 bar, and 4 bar show the pressure difference is 0.00 bar, 0.01 bar, 0.01 bar, 0.00 bar, -0.01 bar, 0.02 bar in respectively. Meanwhile, simulation results at input pressures of 4 bar, 125 bar, and 154 bar show the maximum stress values received by the expansion tank are 1.090 ×10^7 N/m^2, 3.405 ×10^8 N/m^2, 4.195 ×10^8 N/m^2, respectively. Based on the analysis results, it can be concluded that the expansion can be used for experiments.